Phase-Specific Nutritional Therapy in Critical Illness: When Protein May Help and When It May Harm, from Acute Metabolic Adaptation to Post-ICU Recovery - Mircea Stoian; Adina Stoian; Claudia Bănescu; Sergio Rares Bandilă; Alina Danilesco; Hajnal Finta; Leonard Azamfirei (Nutrients, 2026)
Background: Nutritional support in critically ill patients remains one of the most debated aspects of intensive care medicine. Although international guidelines have long recomm.ended early nutritional support with progressive protein delivery, recent clinical evidence has questioned the benefit of aggressive early calorie and protein provision during the acute phase of critical illness, highlighting the need for phase-adapted nutritional strategies. Methods: This narrative review summarizes current evidence on individualized, phase-adapted nutritional therapy in critically ill adults and post-ICU survivors, focusing on protein dose and timing, anabolic resistance, muscle wasting, and nutritional management during recovery. Relevant studies published between January 2011 and June 2026 were identified through structured searches of PubMed/MEDLINE, supplemented by reference screening and forward citation tracking. A total of 59 publications were included in the final narrative synthesis. Results: Recent clinical trials indicate that early high-dose protein administration does not consistently improve survival or functional outcomes and may be associated with harm in selected patient subgroups, particularly those with acute kidney injury, severe organ dysfunction, or shock. More conservative early calorie and protein delivery during the early acute phase has been associated with improved gastrointestinal tolerance and faster clinical stabilization without increasing mortality. Complementary mechanistic evidence supports these findings, highlighting persistent endogenous energy production, anabolic resistance, impaired protein utilization, and reduced autophagy during early critical illness. In contrast, the post-ICU recovery phase is characterized by ongoing muscle wasting, weakness, reduced oral intake, and persistent nutritional deficits, while structured nutritional support after ICU discharge remains inconsistently implemented. Conclusions: Current evidence increasingly supports an individualized, phase-adapted approach to nutritional therapy rather than uniform early aggressive calorie and protein targets. Nutritional strategies should consider illness severity, metabolic phase, organ dysfunction, gastrointestinal tolerance, and recovery trajectory. Further studies are needed to define optimal nutritional targets during post-ICU recovery. An evidence-informed practical framework for phase-adapted nutritional therapy is proposed.